CARACTERIZAÇÃO E ISOLAMENTO DE MICRORGANISMOS DE CHÁ DE KOMBUCHA - FANTIN, Fabio Luiz; SOARES, Fabiana Andreia Schafer de Martini; Souza, Edson Luiz de (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
Kombucha fermentation is a spontaneous and complex process, and several factors can influence the microbial and physicochemical composition. Many people produce this drink by hand with little or no control of the physicochemical and microbiological characteristics, often using SCOBY for handcrafting cultures of bacteria and fungi without identifying the microorganisms present. The objective of the present study was to evaluate the predominant microbiota at different times of fermentation in Kombucha tea obtained from green tea, as well as to identify the variation in the levels of physicochemical parameters in this beverage during fermentation and storage. Each batch of Kombucha was fermented for up to 15 days at room temperature, remaining covered with a paper towel. Microbiological parameters such as counting acetic, lactic, Streptococcus and yeast bacteria, as well as physicochemical parameters such as pH, acidity and soluble solids of Kombucha tea were measured on different days of fermentation and storage. There was growth of acetic and lactic bacteria and yeast from the sixth day of the fermentation process. The highest bacterial and yeast counts were 8.9 log 10 CFU.mL-1 and 8.5 log 10 CFU.mL-1, respectively, obtained on the fifteenth day of fermentation. During the Kombucha storage process, the bacterial and yeast counts remained constant and did not differ significantly during this period, not exceeding the values ​​found during the fermentation process. It was also observed during fermentation and storage the presence of Gram-positive bacteria with probiotic potential, such as Streptococcus spp, reaching maximum levels of 7.0 log10 CFU.mL-1. During fermentation there was a gradual increase in acetic acid concentration, stabilizing from the ninth day of fermentation. The pH decreased throughout the fermentation due to the production of organic acids. Conclusion: The pH levels, as well as the identification and quantification of bacteria and yeasts show that the drink is safe and can have probiotic potential for humans. The difference in microbial composition found in this process is associated with the matrix used in the preparation of Kombucha and the origin of SCOBY, in addition to the fermentation conditions. The acidity contents contribute to obtaining sensory pleasant beverages and a favorable environment for the development of microorganisms with probiotic potential.